Kebijakan Pengelolaan Air Limbah Dalam Penanganan Limbah Batik Di Kota Pekalongan - Yuki Aliffenur Romadhon (Insignia: Journal of International Relations, 2017)
AbstractSince batik is recognized by UNESCO as a nation heritage, batik industry in Pekalongan is increasing, but it caused environmental issues. Then, the government of Pekalongan issued local regulation No. 9 of 2015 about waste water management to minimalized the waste impact in Pekalongan. The sustainable development can be meant as a development concept which fulfills needs of the present without forfeiting the fulfillment rights of needs for future generation. There are three understanding apects in the sustainable development, such as social aspect, economy and environment. Generally, the implementation of local regulation No. 9 of 2015 about waste water management in Pekalongan is a balancer of the sustainable development from batik industry which has been done. There are three sustainable development principles which are suitable with local regualation No. 9 of 2015, such as principle of intergenerational equity, principle of integration between environmental protection and development, and principle of preventive measure. In its implementation, these principles have been already done, but the use of IPAL which has not been maximized caused less water quality standard and become an indication of river pollution.Keywords: batik, waste water, local regulation, sustainable development AbstrakSemenjak diakuinya batik oleh UNESCO sebagai warisan bangsa, industri batik di Kota Pekalongan semakin meningkat, namun hal tersebut menimbulkan peramasalahan lingkungan. Pemerintah Kota Pekalongan kemudian mengeluarkan Perda No 9 tahun 2015 tentang pengelolaan Air Limbah guna meminimalisisr dampak limbah di Kota Pekalongan. Pembangunan berkelanjutan dapat diartikan sebagai konsep pembangunan yang memenuhi kebutuhan masa kini tanpa mengorbankan hak pemenuhan kebutuhan-kebutuhan pada generasi yang akan datang. Terdapat tiga aspek pemahaman dalam pembangunan berkelanjutan, yaitu aspek sosial, ekonomi dan lingkungan. Secara umum implementasi Perda Kota Pekalongan No 9 Tahun 2015 Tentang Pengelolaan Air Limbah merupakan suatu penyeimbang dari pembangunan berkelanjutan dari industri batik yang telah terlaksana. Terdapat tiga prinsip pembangunan berkelanjutan yang sesuai dengan Perda No 9 Tahun 2015, yaitu prinsip keadilan antar generasi (Intergenerational equity), Prinsip Keterpaduan antara Perlindungan Lingkungan Hidup dan Pembangunan, dan prinsip tindakan pencegahan. Pada implementasinya, semua sudah terlaksana, namun penggunaan IPAL yang belum maksimal sehingga menimbulkan kadar baku mutu air diatas yang seharusnya dan menjadi indikasi pencemaran sungai.Kata-kata kunci: batik, air limbah, peraturan daerah, pembangunan berkelanjutan